PERSEPSI KEADILAN DALAM PEMULIHAN LAYANAN PADA KEPUASAN YANG DIMODERASI GENDER, SERTA DAMPAK TERHADAP NIAT MENGINAP KEMBALI DAN WOM - Yasta Vinartha, Raka; Sri Suprapti, Ni Wayan; Gede Sukaatmadja, Putu (Buletin Studi Ekonomi, 2016)
The Effect of Fairness Perception to Satisfaction After Complaints and The Impact on The Intent To Stay Back and WOM. This research aims to clarify the relationship between the three perceptions of fairness experienced by customers with post-recovery service satisfaction and the satisfaction of the behavioural effects of post-recovery service and the intention of revisiting and the willingness to deliver a positive recommendation (WOM). This study also discusses the role of gender in moderating the relationship between perceptions of fairness with post-service satisfaction. Data were obtained from 142 hotels’ customers (foreign tourists) who stay at five-star hotels and have experienced on disappointed services. Data were collected using questioner and subsequently analyzed using descriptive statistics and inferential statistics such as Analysis of Partial Least Square (PLS). The results showed that: (1) distributive fairness has no impacts on customer satisfaction after complaints; (2) procedural fairness and interactional fairness impact positively satisfaction after complaints (3) Satisfaction after handling complaints effect positively the intention on staying back and WOM. (4) Gender does not strengthen and/or not weaken the perception of fairness to the satisfaction of post complaints.   Keywords: perception of fairness, satisfaction after complaints, intent to stay back, WOM, gender
Keywords: perception of fairness, satisfaction after complaints, intent to stay back, WOM, gender